THE INFLUENCE OF CHARACTER EDUCATION ON THE LEARNING ACHIEVEMENT OF STUDENTS AT THE AL-AZHAR ASY-SYARIF BOARDING SCHOOL - Masitah, Widya (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to see the effect of character education on student achievement in class IX at the Al-Azhar Asy-Syarif Islamic boarding school. The total population of class IX was 150 students and the sample in this study was taken 25% of the total population of 39 people. This research is a quantitative study using simple linear regression analysis techniques. The results obtained in this study are that there is an influence of character education on student achievement. This can be seen from the significance value of 0.002 0.05 or it can also be proven by the t count value of 3.424 t table 2.026. The effect of character education on student achievement contributes 24.1%. This means that 75.9% of student achievement is influenced by other factors not examined in this study.